Analisis Pengaruh Suplementasi 25-Hydroxycholecalciferol terhadap Performa Pertumbuhan Ayam Broiler dalam Kondisi Komersial di Jawa Barat, Indonesia: Analysis of Supplemental 25-Hydroxycholecalciferol on Growth Performance of Broiler Chicken Raised Under Commercial Conditions in West Java, Indonesia (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
A large-scale commercial production trial was conducted to evaluate the effect of supplemental 25-hydroxycholecalciferol (25(OH)D3) on the growth performance of broilers.  A total of 100,000 day-old mixed-sex Cobb 500 broilers were allocated equally to 20 farms with 5000 broilers each.  Two experimental diets were prepared:  1) Control diet [(3000 IU D3 kg diet-1 + 2760 IU D3 kg diet-1) = total 5760 IU D3 kg diet-1] and 2) Experimental diet [(3000 IU D3 kg diet-1 + 69 mcg 25(OH)D3 kg diet-1 = 2760 IU D3 equivalent kg diet-1) = total 5760 IU D3 kg diet-1].   The design used a randomized block design with Multivariate Analysis of Covariance analysis method The results showed that broilers chickens fed supplemental 25(OH)D3 significantly gained faster, more efficient feed conversion and lower mortality rate from 0 to 14 days when compared to those fed without 25(OH)D3 supplementation.   Moreover, the relative growth on the diet supplemented with 25(OH)D3 at 7 days was significantly (p